SÔBRE A IDENTIFICAÇÃO PRECOCE DO SEXO EM PINTOS RHODE ISLAND RED - Viana, J. de A. Carneiro; Briquet Junior, Raul (REVISTA DE AGRICULTURA, 2016)
SÔBRE A IDENTIFICAÇÃO PRECOCE DO SEXO EM PINTOS RHODE ISLAND RED